2019
DOI: 10.1097/ta.0000000000002095
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital tourniquet use in penetrating extremity trauma: Decreased blood transfusions and limb complications

Abstract: BACKGROUND Despite increasing popularity of prehospital tourniquet use in civilians, few studies have evaluated the efficacy and safety of tourniquet use. Furthermore, previous studies in civilian populations have focused on blunt trauma patients. The objective of this study was to determine if prehospital tourniquet use in patients with major penetrating trauma is associated with differences in outcomes compared to a matched control group. METHODS An 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 14 publications
3
90
0
1
Order By: Relevance
“…For the important outcome of complications/adverse effects (including compartment syndrome nerve palsy, fasciotomy, thromboembolic episodes), we identified very low-certainty evidence (downgraded for serious risk of bias and imprecision) from 3 prehospital civilian cohort studies 148,151,152 of 1420 participants. Study heterogeneity prevented combining results for meta-analysis.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…For the important outcome of complications/adverse effects (including compartment syndrome nerve palsy, fasciotomy, thromboembolic episodes), we identified very low-certainty evidence (downgraded for serious risk of bias and imprecision) from 3 prehospital civilian cohort studies 148,151,152 of 1420 participants. Study heterogeneity prevented combining results for meta-analysis.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…We identified very low-certainty evidence (downgraded for serious risk of bias) from 5 prehospital civilian cohort studies 145,148,151,152,157 of 1686 participants reporting the complication of amputation. Study heterogeneity prevented combining the results for meta-analysis, and all reported similar amputation rates with the use of tourniquets compared with the use of direct manual pressure alone.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The tourniquet is to be torn and fixed until the bleeding stops and the time point of application is documented. In a retrospective study, tourniquet use was associated with improved cardiocirculatory stability at hospital admission (BPsyst 120 ± 2 vs. 112 ± 2 mm Hg, p = 0.003) and reduced transfusion requirement (packed red blood cells [pRBC]: 2.0 ± 0.1 vs. 9.3 ± 0.6, p < 0.001; fresh frozen plasma concentrates [FFP]: 1.4 ± 0.08 vs. 6.2 ± 0.4, p < 0.001) along with a non-increased risk for complications, e.g., nerve injuries and infections [20]. With increasing magnitude of injury, the occurrence of displaced pelvic injuries with active bleeding mostly from the venous peritoneal plexus increases; of note, only 10-15% of all pelvic bleedings are arterial [21,22].…”
Section: Prehospital Management Of Trauma Hemorrhagementioning
confidence: 99%
“…Âèêîðèñòàííÿ êðîâîñïèííèõ äaeãóò³â ç ìåòîþ çóïèíêè êðîâîòå÷³, çà äàíèìè äîñë³äaeåíü [14], º áåçïå÷íèì òà ïîêðàùóº ðåçóëüòàòè ë³êóâàííÿ. Ðàçîì ç òèì ó òàêèõ ïîñòðàaeäàëèõ ìîaeëèâèé ðîçâèòîê ðàáäîì³îë³çó òà ñèñòåìíèõ çì³í [15].…”
Section: ïîñòàíîâêà ïðîáëåìè ³ àíàë³ç îñòàíí³õ äîñë³äAeåíü òà ïóáë³êàö³éunclassified